Peningkatan Kreativitas dan Hasil Belajar IPA Melalui Model Project based Learning Pada Siswa Kelas V - Faudati, Mirva; Septiyanti, Isnani Fauziah; Sholihin, Adnan; Dewi, Novi Asmarani Kusuma; Nisa, Ana Fitrotun (Universitas Sarjanawiyata Tamansiswa, 2024)
This research aims to increase science students' creativity and learning outcomes through Project Based Learning. The subjects of this research consisted of 10 students from one of the elementary schools in Kapanewon Samigaluh, Kulon Progo Regency, consisting of 6 boys and four girls. The study uses classroom action research methods. The research results show increased creativity and learning outcomes in each cycle. In the first cycle, students' creativity in making diorama projects reached 60% and was included in the quite creative category. In cycle II, there was an increase in student creativity in making diorama projects to 80% in the creative type. Furthermore, students' science learning outcomes in cycle I reached 50% with an average score of 76.6. In cycle II, there was an increase in the completeness of students' science learning outcomes to 80% with an average score of 83.3. Based on these findings, it can be concluded that applying Project Based Learning improves students' creativity and science learning outcomes.